Partitioning of Ce, as a simulant for Pu, in a multiphase ceramic nuclear waste form. Issue 10 (9th June 2020) - Zhang, Zhaoming; Spiers, Kathryn M.; Vance, Eric R.; Davis, Joel
Abstract: A pyrochlore‐rich multiphase ceramic waste form was prepared by the alkoxide‐route and consolidated by sintering in air. Cerium (Ce) was used as a surrogate for plutonium (Pu), which was found in both the major pyrochlore and minor perovskite phases, but not the minor rutile phase. A synchrotron‐based fluorescence X‐ray absorption near‐edge spectroscopy (XANES) imaging technique was employed to determine the Ce oxidation state in each of the two Ce‐containing phases. It was shown that the major pyrochlore phase contains only tetravalent Ce, whereas the minor perovskite phase incorporates exclusively trivalent Ce. The effect of sintering atmosphere was also investigated, which revealed a very different phase assemblage when sintered in argon (Ar). A major perovskite phase was produced under Ar with a minor zirconolite‐4M phase, both containing trivalent Ce. The composition of the minor rutile phase remained the same whether it was sintered in air or Ar. The results demonstrate the importance of controlling the oxidation state of multivalent waste ions in the design of ceramic waste forms.